1992
DOI: 10.4294/jpe1952.40.343
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional P and S Wave Velocity Structure in the Focal Region of the 1984 Western Nagano Prefecture Earthquake.

Abstract: The detailed three-dimensional P and S wave velocity structure in the focal region of the 1984 Western Nagano Prefecture Earthquake occurring close to an active volcano, Mt. Ontake, central Japan, is derived from a tomographic inversion of travel time data obtained by the 1986 Joint Seismological Research in Western Nagano Prefecture. The data set includes 7,693 P-wave and 6,070 S-wave arrival times observed at 49 stations from 212 local earthquakes and 2 explosions. The velocities in the shallow portion of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Consequently the high velocity anomalies show high resistivity. Hirahara et al (1992) investigated 3-D velocity structure in the source region of the 1984 Western Nagano Prefecture Earthquake. They found that the areas with large dislocations corresponded to those with relatively low velocities on the fault plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently the high velocity anomalies show high resistivity. Hirahara et al (1992) investigated 3-D velocity structure in the source region of the 1984 Western Nagano Prefecture Earthquake. They found that the areas with large dislocations corresponded to those with relatively low velocities on the fault plane.…”
Section: Discussionmentioning
confidence: 99%
“…Hirahara et al (1992) studied the relationship between the slip distribution of the 1984 Western Nagano Prefecture Earthquake (Mj = 6.9) and the 3-D velocity structure in the source region. They found that the area with large dislocations corresponded to low velocity anomalies on the fault plane.…”
Section: Introductionmentioning
confidence: 99%
“…It was intended to understand the swarm activities and the mainshock-aftershock activity which occurred in the same area. This is the first joint observation for the inland earthquake by many institutions with modern instruments including seismic, geodetic, gravity measurements (e.g., Horiuchi et al, 1992;Hirahara et al, 1992;Kasaya et al, 2002). In the later 5-year programs, the joint observations, where many institutions jointed with their instruments and sheared the data, were conducted several times; in the area of Japanese Alps in central Honshu (e.g., Matsubara et al, 2000), Nikko area in northeastern Honshu (Horiuchi et al, 1997), Tohoku area in northeastern Honshu (e.g., Nakajima et al, 2001), Hokkaido (Katsumata et al, 2003), and southwestern Honshu, Japan.…”
Section: The Blue Print and The First National Earthquake Prediction mentioning
confidence: 96%
“…Using data obtained by this dense joint network, Horiuchi et al (1992), Yamazaki et al (1992), Hirahara et al (1992) and Ikami et al (1992) determined detailed hypocenter locations, spatial distribution of focal mechanisms, and three-dimensional velocity structure, respectively.…”
Section: Real-time Operationmentioning
confidence: 99%